1997
DOI: 10.1042/bj3270161
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification and characterization of Arabidopsis thaliana acetohydroxyacid synthase

Abstract: Acetohydroxyacid synthase (EC 4;1;3;18) is the enzyme that catalyses the first step in the synthesis of the branched-chain amino acids valine, leucine and isoleucine. The AHAS gene from Arabidopsis thaliana with part of the chloroplast transit sequence removed was cloned into the bacterial expression vector pT7-7 and expressed in the Escherichia coli strain BL21(DE3). The expressed enzyme was purified by an extensive procedure involving (NH % ) # SO % fractionation followed by hydrophobic and anion-exchange ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 51 publications
5
76
1
Order By: Relevance
“…The temperature dependence of the acetohydroxyacid synthase activity was bell shaped, in the range of 10-50 o C. The enzyme has low activity at low and high temperature, respectively ( Figure 2B), which implied that temperature can effect the enzymatic activity in the reaction. The optimum temperature (37 o C) and pH (7.5) results for B. anthracis AHAS are consistent with Escherichia coli I AHAS (pH 7.5) 13 and permeabilized yeast cell (pH 7-8).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The temperature dependence of the acetohydroxyacid synthase activity was bell shaped, in the range of 10-50 o C. The enzyme has low activity at low and high temperature, respectively ( Figure 2B), which implied that temperature can effect the enzymatic activity in the reaction. The optimum temperature (37 o C) and pH (7.5) results for B. anthracis AHAS are consistent with Escherichia coli I AHAS (pH 7.5) 13 and permeabilized yeast cell (pH 7-8).…”
Section: Discussionsupporting
confidence: 53%
“…14 Lately AHAS has been intensively studies, [15][16][17] since AHAS has been known a potential target for various classes of herbicides. Therefore, the inhibition of B. anthracis AHAS by the three classes of herbicides, Londax (a sulfonylurea), Cadre (an imidazolinone), and TP (a triazopyrimidine) was determined.…”
Section: Discussionmentioning
confidence: 99%
“…Acetolactate synthase (EC 2.2.1.6) catalyzes the first step in the pathway from 2-oxobutanoate to isoleucine (Figure 11) and also the first step in the parallel biosynthetic pathway leading from pyruvate to valine and leucine (Coruzzi and Last, 2000). A. thaliana At3g48560 (CSR1) encodes the large, catalytic subunit of acetolactate synthase (Haughn and Somerville, 1990;Sathasivan et al, 1990;Chang and Duggleby, 1997), and At2g31810 encodes the small, regulatory subunit (Lee and Duggleby, 2001). Another gene, At5g16290, likely also encodes an acetolactate synthase small subunit, but has not yet been characterized.…”
Section: Isoleucine Biosynthesismentioning
confidence: 99%
“…This prediction agrees with the findings of the majority studies and K m values in the range 1 to 20 mM are usually reported (summarized in 14 AHAS from Arabidopsis thaliana has also been reported to display negatively cooperative kinetics (0.6 Hill coefficient) with respect to pyruvate concentration and there appeared to a short lag time of 1-2 min before full activity of the enzyme was attained. 15 AHAS activated with regulatory subunit displayed a hyperbolic substrate saturation curve 23 indicating that reconstitution with the regulatory subunit abolished the negative cooperativity. Pyruvate saturation curves from tobacco recombinant AHAS displayed Michaelis-Menten 24 and non-Michaelis-Menten kinetics.…”
Section: +mentioning
confidence: 99%